Relevant updates in systemic mastocytosis. (June 2019) - Coltoff, Alexander; Mascarenhas, John
Highlights: SM is a rare MPN characterized by a proliferation of clonal mast cells. KITD816V is a driver mutation found in the majority of patient with SM. Treatment focus of indolent SM is symptom management. Cytoreductive treatment is required for patients with advanced SM. The development novel KIT inhibitor has improved the outcomes of advanced SM. Abstract: Systemic Mastocytosis (SM) is a rare myeloproliferative neoplasm (MPN) that is characterized by a clonal proliferation of mast cells (MCs). The symptoms and clinical presentation of SM are the result of both MC proliferation as well as activation and degranulation, causing hyperactive and over-exaggerated hypersensitivity responses, as well as organ infiltration by pathogenic MCs. The clinical presentation and course of SM is varied and organ involvement can lead to significant morbidity and mortality in some cases. The subtypes of SM include indolent SM (ISM), smoldering SM (SSM), aggressive SM (ASM), SM with associated hematologic neoplasm (SM-AHN) and mast cell leukemia (MCL) and survival can range from normal in the case of ISM to months in MCL. The treatment of indolent forms of SM is largely focused on addressing symptom burden (B findings), while cytoreductive agents and more recently molecularly targeted agents are employed to reduce MC burden and reverse associated organ dysfunction (C findings). Although the pathogenesis of SM is multi-factorial, the acquisition of KIT D816 V is a relatively frequent mutational event and serves as the target of novel agents. The recent approval of midostaurin for the treatment of advanced SM has brought awareness to this disease and energized further drug development efforts. Expanding our understanding of the underlying molecular mechanisms of SM will continue to inform future therapeutic approaches.